Urban Aesthetics of Madrid as a Film Scenario of the Quinqui Cinema - Codesido Linares, Váleri; García García, Francisco (Street Art & Urban Creativity, 2025)
This research analyzes cine quinqui and its representation of the city through an interrelational narrative approach. The study develops the characteristics that articulate an urban mode of representation associated with cine quinqui. A sample of cine quinqui films is selected to examine the construction of the city, highlighting the typological and topological differences of their settings in the films Deprisa, deprisa, Navajeros, Chocolate, and Maravillas. These films reflect a Madrid undergoing architectural and real estate expansion, where vacant lots appear as a constant element. The creation of the quinqui character is intrinsic to the city they inhabit, but paradoxically, they have no place within it. This thesis will feed much of the dystopian aesthetic of cine quinqui during the Transition period by depicting a city that harbors a youth disconnected from the preceding generation.